Do neonatal intensive care unit (NICU) health workers know about retinopathy of prematurity (ROP)? A qualitative study at a Regional Referral Hospital in Uganda - Henry Muwonge; Innocent Ayesiga; Primrose Magala; Tom Didimus Ediamu; Hana El Diwany; Ian LY Yeung; Alex Wasomoka; Phillip Musoke; Elias Musiime; Abraham Tumwesigye; Pius Atwau; Noreen Atwijukire; et al. (BMJ Paediatrics Open)
Introduction Retinopathy of prematurity (ROP) is a significant cause of blindness and visual impairment in preterm infants globally, particularly in low-income and middle-income countries. ROP is associated with prematurity, and with the increase in the survival of preterm infants, its global burden continues to rise. However, there is limited information available on health workers’ perspectives regarding ROP in Uganda.Methods This qualitative study explored health workers’ experiences regarding ROP in the neonatal intensive care unit (NICU) at Hoima Regional Referral Hospital. This study involved in-depth interviews with eight health workers working in the NICU. We examined individual, facility and national factors that could impact the health workers’ perspectives on ROP at the hospital. The data obtained were transcribed and coded, and themes were generated for further analysis.Results We identified key barriers and facilitators to effective ROP care. Four major themes emerged from the analysis: (1) Knowledge and awareness of ROP, (2) Challenges and limitations in implementing the ROP screening programme, (3) Training and guidelines for ROP screening and treatment and (4) Recommendations for ROP prevention screening and management. ROP awareness, knowledge of ROP and witchcraft and ROP were identified as specific subthemes under the knowledge and awareness of ROP theme.Discussion and conclusion This study reveals significant gaps in health workers’ knowledge and awareness of ROP. Limited access to essential equipment and specialised personnel may further limit ROP screening capacity. We suggest implementing a multidisciplinary team approach, continuous professional development and establishing national ROP guidelines. We recommend developing a formal training structure and syllabus for ROP screening. The training can enhance task shifting among health workers in areas without specialised health workers. Addressing the identified barriers is crucial for improving the care and outcomes for preterm infants in Uganda and similar settings.